2022
DOI: 10.3389/fbioe.2022.897185
|View full text |Cite
|
Sign up to set email alerts
|

Arnica Montana L. Supercritical Extraction Optimization for Antibiotic and Anticancer Activity

Abstract: Arnica montana L. flower heads are known for their antioxidant, antimicrobial, and anticancer activity. The aim of this work was to optimize the process of supercritical CO2 extraction, to achieve high extraction yield and high content of biologically active components, and to confirm the antimicrobial and anticancer activity of the extract. The influence of pressure and temperature on the total phenolic content, antioxidant activity, and proanthocyanidin content was evaluated. The pressure and temperature wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…In some cases, medicinal plants can even reverse antibiotic resistance. In addition to bactericidal and bacteriostatic effects, medicinal plants have been reported to present other mechanisms, such as antiadhesive activity [ 224 , 225 , 226 ], the inhibition of bacterial growth [ 227 , 228 ], anti-biofilm-formation activity [ 229 , 230 ], the inhibition of motility [ 231 , 232 ], the protection of host urinary cells [ 233 ], and the enhancement of antibacterial immunity. In Table 3 , we summarize recently studied plants that achieved positive results against UPEC.…”
Section: Treatment Of Urinary Tract Infectionsmentioning
confidence: 99%
“…In some cases, medicinal plants can even reverse antibiotic resistance. In addition to bactericidal and bacteriostatic effects, medicinal plants have been reported to present other mechanisms, such as antiadhesive activity [ 224 , 225 , 226 ], the inhibition of bacterial growth [ 227 , 228 ], anti-biofilm-formation activity [ 229 , 230 ], the inhibition of motility [ 231 , 232 ], the protection of host urinary cells [ 233 ], and the enhancement of antibacterial immunity. In Table 3 , we summarize recently studied plants that achieved positive results against UPEC.…”
Section: Treatment Of Urinary Tract Infectionsmentioning
confidence: 99%
“…Not only the plant part but also the plant age has an influence on the chemical composition of secondary metabolites and anticancer activity. Žitek et al [ 24 ] reported apoptotic activity of A. montana flower head extracts against melanoma WM-266–4 cells. In turn, Flórez-Fernández et al [ 68 ] showed cytotoxic properties against colorectal cancer HCT-116 and pancreatic adenocarcinoma PSN1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The above-ground and underground parts of this special medicinal plant are characterized by the presence of valuable secondary metabolites, including sesquiterpene lactones, flavonoids, terpenoids, phenolic acids, and essential oils [ 13 , 14 , 15 , 16 , 17 ]. Its inflorescences, achenes, leaves, rhizomes, and roots are a rich source of raw material, with antibacterial, antifungal, antiseptic, anti-inflammatory, antiradical, antisclerotic, antioxidant, and antitumor properties [ 5 , 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a source of extremely interesting secondary metabolites (SMs) characterized by antioxidant and anticancer activity, medicinal plants are of great interest to researchers around the world [1][2][3][4]. In recent years, new sources of SM in medicinal plants have been identified and investigated [5,6], and the introduction of these plants to cultivation has Appl.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the quantity and quality of the RM can be modified based on the knowledge of the biology and ecology of the species and with the use of agricultural tools. In the case of Arnica spp., different plant parts can be used, i.e., flower heads, rhizomes, or all underground parts of plants characterized by varied contents and different chemical compositions of such SMs as total phenolics, flavonoids (Fs), phenolic acids, sesquiterpene lactones (SLs), and essential oils (EOs) [23,24] with their broad biological activity [4,11,[25][26][27][28]. Analyses of individual parts of the plant revealed the highest antiradical activity of A. montana flower head tincture.…”
Section: Introductionmentioning
confidence: 99%